Penyelesaian Split Delivery VRP dengan Ant Colony Optimization (Studi Kasus: Pengiriman Produk di PT Sinarmas Distribusi Nusantara) - Ginting, Anita Br; Fayaqun, Reza; Bisma, Muhammad Ardhya (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT Sinarmar Distribusi distributes its products to all Distribution Center (DC) every day. Currently PT Sinarmas Distribution Nusantara uses a predetermined route every day using Colt Diesel Double vehicles with maximum transport capacity of 500 cartons. Currently the number of products carried by each vehicle never reaches its maximum carrying capacity. PT Sinarmas Distribusi Nusantara wants vehicle transport capacity to be used optimally. This route problem at PT Sinarmas Distribusi Nusantara can be defined as Split Delivery Vehicle Routing Problem (SDVRP). Ant Colony Optimization (ACO) is a metaheuristic that can be used to solve SDVRP. By using ACO the resulting route is always shorter than the current route and the number of vehicles used is smaller.